Addressing the designer selection problem in mega infrastructure projects using hybrid multi-criteria decision-making methods - Demirci, Fehmi Samet; Okudan, Ozan; Isik, Zeynep (EMERALD GROUP PUBLISHING LTD, 2026)
PurposeThis study aims to develop a decision-support model to help decision-makers identify the most suitable designers for mega infrastructure projects (MIPs). The proposed model was integrated with an extensive set of criteria and a comparison mechanism that enables decision-makers to compare various design firms for more informed decisions.Design/methodology/approachAt the outset, a comprehensive literature review was conducted to identify selection criteria that should be considered during the designer selection process. Then, focus group discussion (FGD) sessions were conducted with the participation of experts who have diverse experience in MIPs. During these sessions, the experts verified the identified selection criteria and proposed additional criteria that have not been proposed in the literature. Next, the fuzzy analytic hierarchy process analysis was conducted to determine the weights of the selection criteria and provide input for the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) analysis. A consistency analysis was then performed to verify the reliability of the dataset. The proposed model was tested and demonstrated through a hypothetical case study and TOPSIS analysis in the next step. Finally, a sensitivity analysis was performed to verify the results and the model.FindingsThe comprehensive literature review and FGD sessions yielded a thorough list of criteria. Decision-makers can adopt these criteria to obtain data from designers who bid for a particular MIP. Results also pinpointed that focusing only on financial criteria in the designer selection could lead to misguided decisions. Instead, a wide range of aspects, such as past performance and technical capability, should be considered. Furthermore, criteria related to cash flow, recent experience, successful collaborations, adherence to contracts and non-financial resources were particularly deemed the most critical, necessitating considerable attention from the decision-makers. Lastly, the case study results highlighted that the proposed model offers significant potential for enhancing the systematic selection of designers in MIPs.Originality/valueDelays and cost overruns have long been persistent characteristics of the MIPs, a phenomenon often described as the megaprojects paradox. As one of the most critical causes of delays and cost overruns, design failures jeopardize the deliverables of MIPs. Thus, these projects should be designed precisely to eliminate all faults and maximize efficiency in the latter stages. Existing studies have been widely focused on improving the contractor and subcontractor selection process of MIPs while providing little knowledge to address design-related issues. Thus, this study presents significant theoretical and practical contributions. It is one of the earliest attempts to examine the key qualifications the designers should embody in MIPs.
Keywords: Mega infrastructure projects; Design management; Designer selection; Decision-support model; Fuzzy AHP; TOPSIS; Case study; CONTRACTOR SELECTION; SUBCONTRACTOR SELECTION; SUPPLIER SELECTION; CONSTRUCTION PROJECTS; SUPPORT-SYSTEM; TOPSIS METHOD; FOCUS GROUP; FUZZY-SET; MODEL; AHP; Engineering; Business & Economics